Social Media Marketing Strategy in Increasing Customer Engagement of Taman Safari Ndonesia Bogor (Case Study on Instagram @Taman_Safari) - Jessica Bong Natasha; Chininta Rizka Angelia; Daniel Susilo (Indonesian Journal of Business Analytics, 2023)
With  the  pandemic  condition,  Taman  Safari  Indonesia  Bogor  is  also  looking  for  ways  to  increase  customer  engagement.  One  of  the  methods  used  is  to  carry  out  a  social  media  marketing  strategy  with  promotions  through  social  media  to  increase  customer  engagement.  This  research  was  conducted  to  determine  the  social  media  marketing  strategy  in  increasing  customer  engagement  at  Taman  Safari  Indonesia  Bogor  in  the  case  study  of  Instagram  @taman_safari.  The  concept  used  in  this  research  is  the  social  media  marketing  strategy  from  Tuten  &  Solomon  (2018)  and  customer  engagement  from  Cuillierier  (2016)  and  Zyminkowska  (2019).  This research uses  descriptive  qualitative research  and  case  study  methods.  The data collection  of  the  research  carried  out  were  interviews  and  documentation.   Interviews were  conducted  in-depth  (in-depth  interviews)  to  research  participants.  The criteria  for  participants  is  to  have  to  work  at  Taman  Safari  Indonesia  Bogor  for  a  period  of  more  than  1  year.  The  results  of  this  study  indicate  that  in  increasing  customer  engagement,  Instagram  @taman_safari  has  implemented  a  social media marketing strategy that is structured through specific stages.